2020
DOI: 10.3390/microorganisms8060807
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Scardovia wiggsiae Biofilm by Original Scanning Electron Microscopy Protocol

Abstract: Early childhood caries (ECC) is a severe manifestation of carious pathology with rapid and disruptive progression. The ECC microbiota includes a wide variety of bacterial species, among which is an anaerobic newly named species, Scardovia wiggsiae, a previously unidentified Bifidobacterium. Our aim was to provide the first ultrastructural characterization of S. wiggsiae and its biofilm by scanning electron microscopy (SEM) using a protocol that faithfully preserved the biofilm architecture and allowed an inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 63 publications
1
55
1
Order By: Relevance
“…Staining with other heavy-metal reagents such as Ruthenium Red and RuO 4 may provide more specific contrasting of ECM components. As stated in [ 50 ], they also confirmed that sample drying using HDMS was a valuable and rapid alternative to conventional chemical fixation and drying. We tested the OsO 4 -RR-TA-IL protocol on a Candida albicans biofilm from an ex vivo sample (unpublished results) and also analyzed the images obtained with a four-quadrant method [ 100 ] by Hitachi 3D Mountains Map software (Digital surf, France).…”
Section: Scanning Electron Microscopy Techniques Applied To Biofilsupporting
confidence: 61%
See 4 more Smart Citations
“…Staining with other heavy-metal reagents such as Ruthenium Red and RuO 4 may provide more specific contrasting of ECM components. As stated in [ 50 ], they also confirmed that sample drying using HDMS was a valuable and rapid alternative to conventional chemical fixation and drying. We tested the OsO 4 -RR-TA-IL protocol on a Candida albicans biofilm from an ex vivo sample (unpublished results) and also analyzed the images obtained with a four-quadrant method [ 100 ] by Hitachi 3D Mountains Map software (Digital surf, France).…”
Section: Scanning Electron Microscopy Techniques Applied To Biofilsupporting
confidence: 61%
“…Conventional SEM and FESEM are the best methods for biofilm visualization if high magnification and high-resolution images are needed to accurately describe biofilm morphology [ 50 , 51 , 52 ]. In comparative analyses, like the evaluation of the anti-biofilm effects of a drug/treatment, it appears as an extremely useful tool [ 11 ], since the results of SEM imaging are highly correlated with those from other analytical methods [ 53 , 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Scanning Electron Microscopy Techniques Applied To Biofilmentioning
confidence: 99%
See 3 more Smart Citations